2020
DOI: 10.1007/s00018-020-03533-8
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the initiation of female meiosis in the mouse at single-cell resolution

Abstract: Germ cell meiosis is one of the most finely orchestrated events during gametogenesis with distinct developmental patterns in males and females. However, in mammals, the molecular mechanisms involved in this process remain not well known. Here, we report detailed transcriptome analyses of cell populations present in the mouse female gonadal ridges (E11.5) and the embryonic ovaries from E12.5 to E14.5 using single cell RNA sequencing (scRNA seq). These periods correspond with the initiation and progression of me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 77 publications
7
41
0
Order By: Relevance
“…A similar analysis from a second scRNA-seq dataset of whole ovaries from earlier E11.5 to E14.5 time points supported these findings (Ge et al 2021) (Fig S1).…”
Section: Taf4b Expression Peaks At E165 In Female Embryonic Germ Cellssupporting
confidence: 70%
“…A similar analysis from a second scRNA-seq dataset of whole ovaries from earlier E11.5 to E14.5 time points supported these findings (Ge et al 2021) (Fig S1).…”
Section: Taf4b Expression Peaks At E165 In Female Embryonic Germ Cellssupporting
confidence: 70%
“…Another is regard to the incorporate of biological replicates [77,78]. Although the biological replicates are suggested to eliminate batch effects, it seems the 1 replicate is still more popular in the single-cell dataset of recent publications [47,61]. In the present study, the application of 1 replicate may be considered as a potential limitation; however, the canonical knowledge in the field of PF formation, as well as the experimental verification, makes us confident for our results.…”
Section: Plos Biologymentioning
confidence: 74%
“…Through using this method, we revealed several TFs at distinct stages, such as Nr3c1, Foxo1, Brca1, Kdm5a, and Kdm5b at the germ cell nest stage; Smarcb1, Hes1, Stat3, and Sox15 during the period of PF assembly; and Foxo3 mainly limited postnatal period (Fig 5). It is worth noting that Nr3c1 has been revealed as the meiotic specific TF in oocyte; furthermore, Brca1, Kdm5a, and Kdm5b have previously been detected in meiotic oocyte [61]. Meanwhile, recent studies have shown that FOXO3 plays a critical role in the maintenance of PF dormancy and Foxo3 knockout lead to follicles overactivation [62][63][64], and the results indicate Foxo3 is a suppressor of PF activation and may be required for their formation.…”
Section: Plos Biologymentioning
confidence: 84%
“…One study subjected the cell populations in female mouse gonads to scRNA-seq to elucidate the molecular mechanism underlying female germ cell development [63]. The genital ridges of the E11.5 mouse embryo and the ovaries of the E12.5, E13.5, and E14.5 mouse embryos were analyzed.…”
Section: Tfs For Sex Determinationmentioning
confidence: 99%